Nocardia choroidal abscess-a Case report with Review of literature - Dave, Prachi Abhishek; Agarwal, Manisha; Sapra, Neelam; Kimmatkar, Prajakta (Nepalese Journal of Ophthalmology, 2018)
Introduction: Nocardia is a common cause of corneal infections but is a rare cause of choroidal abscess. We report a rare case of choroidal abscess, secondary to Nocardia and its management. Case: We report a case of choroidal abscess secondary to Nocardia asteroides species in an immunocompetent young male diagnosed by culture positivity of vitreous biopsy. He was managed by oral trimethoprimsulfamethoxazole and intravitreal Amikacin injections. Conclusion: All the previous reported cases were found to be immunocompromised patients. However, our patient was immunocompetent and the confirmation of diagnosis was done by culture of vitreous biopsy in comparison to a retinochoroidal biopsy, in all other previous cases.